Nowa literatura rumuńsko-włoska. O migracji z Rumunii do Włoch: Badante per sempre [Opiekunka na zawsze] Ingrid Beatrice Coman i Dalla Romania senza amore [Z Rumunii bez miłości] Anci Martinas - Karol Karp (Polilog: Studia Neofilologiczne, 2024)
New Romanian-Italian literature. On Migration from Romania to Italy: Badante per sempre by Ingrid Beatrice Coman and Dalla Romania senza amore by Anca Martinas